Evaluation of drug interaction potential of Labisia pumila (Kacip Fatimah) and its constituents - Manda, Vamshi K.; Dale, Olivia R.; Awortwe, Charles; Ali, Zulfiqar; Khan, Ikhlas A.; Walker, Larry A.; Khan, Shabana I. (Frontiers in Pharmacology, 2014)
Labisia pumila (Kacip Fatimah) is a popular herb in Malaysia that has been traditionally used in a number of women’s health applications such as to improve libido, relieve postmenopausal symptoms, and to facilitate or hasten delivery in childbirth. In addition, the constituents of this plant have been reported to possess anticancer, antioxidant, and anti-inflammatory properties. Clinical studies have indicated that cytochrome P450s (CYPs), P-glycoprotein (P-gp), and Pregnane X receptor (PXR) are the three main modulators of drug-drug interactions which alter the absorption, distribution, and metabolism of drugs. Given the widespread use of Kacip Fatimah in dietary supplements, the current study focuses on determining the potential of its constituents to affect the activities of CYPs, P-gp, or PXR using in vitro assays which may provide useful information towards the risk of herb-drug interaction with concomitantly used drugs. Six compounds isolated from the roots of Labisia pumila (2 saponins and 4 alkyl phenols) were tested, in addition to the methanolic extract. The extract of Labisia pumila showed a significant time dependent inhibition (TDI) of CYP3A4, reversible inhibition of CYP2C9 and 2C19 and a weak inhibition of 1A2 and 2D6 as well as an inhibition of P-gp and rifampicin-induced PXR activation. The alkyl phenols inhibited CYP3A4 (TDI), CYP2C9 and 2C19 (reversible) while saponins inhibited P-gp and PXR. In conclusion, Labisia pumila and its constituents showed significant modulation of all three regulatory proteins (CYPs, P-gp and PXR) suggesting a potential to alter the pharmacokinetic and pharmacodynamic properties of conventional drugs if used concomitantly.